1991
DOI: 10.1111/j.1476-5381.1991.tb09827.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the structure‐binding relationships of antagonists for muscarinic acetylcholine receptor subtypes

Abstract: 1Membranes from rat cerebral cortex, myocardium and extraorbital lacrimal gland were used as sources of M1, M2 and M3 muscarinic acetylcholine receptors respectively and the affinities of seven antagonists for the three subtypes were examined under different experimental conditions. 2 The affinities for the membrane-bound receptors were measured at different ionic strengths and temperatures and compared with those determined on the receptor solubilised in the neutral detergent digitonin or the zwitterionic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…They apparently are not caused by magnesium, and the reported effects of ionic strength on the affinity of gallamine are comparatively small (Pedder et al, 1991). They may be related to the state of aggregation of the receptor, which can exist as oligomers in whole cells (Goin and Nathanson, 2006), in detergent-solubi- The data represented in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…They apparently are not caused by magnesium, and the reported effects of ionic strength on the affinity of gallamine are comparatively small (Pedder et al, 1991). They may be related to the state of aggregation of the receptor, which can exist as oligomers in whole cells (Goin and Nathanson, 2006), in detergent-solubi- The data represented in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…At the moment, the basis for this discrepancy between functional and binding affinity estimates remains unknown. However, a previous study by Pedder et al (1991) revealed a striking divergence in the affinity estimates of the allosteric modulator, gallamine, at M 2 muscarinic receptors depending on the assay conditions used to determine this value. Indeed, differences in the affinity of the modulator spanned almost two orders of magnitude.…”
Section: Parametermentioning
confidence: 99%
“…Indeed, differences in the affinity of the modulator spanned almost two orders of magnitude. It is also worth noting that these same variations in assay conditions had minimal effects on orthosteric ligand affinity estimates (Pedder et al, 1991). Because allosteric sites are, by their very nature, topographically distinct from the orthosteric site on a GPCR, they can be sensitive to ionic changes under conditions where orthosteric ligands are minimally affected.…”
Section: Parametermentioning
confidence: 99%
“…The low-affinity saturable component was also present in centrifugation assays using M 2 CHO cell membranes (data not shown) and is therefore not a specific characteristic of porcine heart membranes. Figure 2B also (Pedder et al, 1991;Trä nkle et al, 1996). The results of the equilibrium and kinetic assays are shown in Fig.…”
Section: [ 3 H]dimethyl-w84 Binding Characteristics Using the New Fimentioning
confidence: 99%